Neurocysticercosis immunodiagnosis: immunoenzimatic assay with antigens covalently bounded on nylon treated resin to detect antibodies in CSF and sera - Vaz, Adelaide José; Ferreira, Antonio Walter (Revista do Instituto de Medicina Tropical de São Paulo, 1988)
The enzyme-linked immunosorbent assay, ELISA, was developed in a new type of support consisting of discs of sinthetic fabric-resin (ELISA-d) with antigenic components of Cysticercus cellulosae covalently bound for detection of antibodies in sera and cerebrospinal fluid (CSF). The support fabric-resin consistis of poliéster fabric coated with crosslinked resin (N-methylol-acrylamide) containing N-methylol groups able to form covalent bounds with functional groups of proteins and polysaccharides which are present in the antigenic saline extract obtained from Cysticercus cellulosae. Sera titer and CSF titer were determined using only one dilution according to the dose-response standard curves obtained. Thirty-eight sera and 74 CSF from patients with confirmed diagnosis of neurocysticercosis and 50 sera and 107 CSF from a control group (patients suffering from neurological disorders other than neurocysticercosis and supposedly healthy individuals) were assayed The sensitivity and the specificity of ELISA-d were determined: 94.7% and 92.0% for sera and 98.6% and 100% for CSF. The ELISA-d test proved to be efficient for the diagnosis of neurocysticercosis, mainly when carried out in CSF, with the advantages of good stability, easy preparation and execution and low cost.